(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The focus of this paper is on the selection of apparently neutral characteristics, refused in several jurisdictions, namely in Europe. The reasons for such refusals are considered in this paper. However, arguments such as the difficulty in distinguishing apparently neutral features from others that are health-related, the recognition that some features are not so neutral after all, and the discredit of genetic determinism are counterarguments that may lead to a different assessment of non-health related reproductive decisions. The premise of this paper is that the prohibition of parental reproductive choices for selecting non-health related features should be reassessed due to the fragility of the arguments invoked against them.